Morphological Variations of the Lungs: A Cadaveric Study - Gautam, Ajeevan; Chaulagain, Rajib; Dhungel, Deepesh (Nepal Medical College Journal, 2021)
The lungs are the organs of respiration which are situated on either side of the heart and other mediastinal contents in its pleural cavity. A fresh lung is spongy, can float in water and crepitates when handled. Lungs are important with respect to its blood circulation. The lungs are divided by fissures into lobes which facilitate movements of lobes in relation to one another. The hilum of each lung is its gateway. In the present study, we aim to assess the morphological variations of human cadaveric lungs at Chitwan Medical College (CMC). An observational study was conducted at dissection hall of anatomy department at Chitwan Medical College from September 2019 to October 2020 after taking ethical approval form Institutional Review Committee of CMC. All the intact 70 lungs present in the department were studied. Photographs of the intact lungs were taken from different surface. The lungs were porus, highly elastic and spongy in texture. On keeping lungs to water tank it got floated. We found 34(80.96%) of the studied specimen of right side had horizontal fissure present in it. The remaining 8 (19.04%) specimens did not have horizontal fissures, while 3 (5.88%) specimens had incomplete fissures. The oblique fissure was not present in 2 (2.38%) of the study specimens. The left side of the study specimen has a variance of 1(4.16%). When the hilum right lung was examined, 40 (95.23%) of the structure had the usual organization pattern. In the left lung, the usual pattern of organization was 21(75%). The differences are thought to be present in the lung’s fissure and hilum. The current study’s findings are therapeutically important. The findings could prove beneficial to cardiovascular and thoracic surgeons.